Living alone decreased calcaneus ultrasound T-score in a large Taiwanese population follow-up study - Lin, Ting-Yi; Chen, Szu-Chia; Geng, Jiun-Hung; Tsai, Hui-Ju (Frontiers in Public Health, 2022)
Background Osteoporosis is associated with many serious health conditions that have a severely negative impact on quality of life, as well as higher rates of morbidity and mortality. Due to the aging society and low birth rate in Taiwan, an increasing number of people are living alone. This longitudinal study was aimed to assess the relationship between living alone and calcaneus ultrasound T-score in a large cohort in Taiwan. Methods A total of 118,853 participants enrolled in the Taiwan Biobank since 2008 to 2016, who had complete calcaneus ultrasound examinations were collected in the baseline study. Of these participants, 26,850 received complete follow-up measurements after a median of 4 years. The T-score (g/cm2) of the calcaneus in the non-dominant foot was measured using ultrasound. Changes in the calcaneus ultrasound T-score (ΔT-score) were calculated as follow-up T-score minus baseline T-score. We analyzed these data in 2022. We used multivariable linear regression analysis to investigate correlation between living alone with baseline T-score and ΔT-score. We also carried out separate analyses for men and women. Results The mean age of the participants was 49.89±10.95 years, and multivariable analysis showed that living alone was significantly correlated to low baseline T-score in whole cohort (β=-0.040; p=0.012) and women (β=-0.055; p=0.023). Furthermore, living alone (coefficient β=-0.049; p=0.048) was significantly correlated to a low ΔT-score after 4 years of follow-up. Conclusion In this large population-based longitudinal study, living alone may be related to low baseline calcaneus ultrasound T-score and ΔT-score. Adopting long-term community-based care policies to increase the activity of people living alone may help to prevent osteoporosis and decrease the risk of fractures in Taiwan.